The comparative biopharmaceutical study of febuxostat solid dosage forms - Mikhail V. Larsky; Denis S. Zolotykh; Aleksei S. Chiriapkin; Vladislav V. Vernikovsky (LLC "MEDIAFORMAT", 2022)
Aim. Biopharmaceutical assessment of various solid dosage forms (capsules and coated tablets) of febuxostat formulations including comparison of excipients used in these dosage forms, disintegration pathways under static conditions, and dissolution kinetic profiles. Methods. The Azurix® coated tablets and Podagrel hard gelatin capsules containing 80 mg of febuxostat were the object of the study. The model of disintegration under static conditions was used to assess disintegration of the dosage forms. Quantification of febuxostat in the samples diring the comparative study of dissolution kinetics was performed by high-performance liquid chromatography. Results. When assessing morphological changes of dosage forms in the static model developed to simulate gastric environment, various desintegration patterns and rates confirmed by the differences in the qualitative composition of the excipients used were defined for these dosage forms. The comparative kinetics study showed different rates of febuxostat release from the studied dosage forms. Conclusion. The findings demonstrate a significant impact of the excipient composition on the behavior of dosage forms in the body environment, particularly on the dosage form desintegration, which in turn defines the rate and degree of the active ingredient release. Thus, the test shows pronounced differences in biopharmaceutical parameters, capable of affecting the studied drugs bioavailability, between two febuxostat dosage forms.